A study of a d-proline peptidomimetic inhibitor of melanoma and endothelial cell invasion through activity towards MMP-2 and MMP-9. Issue 2 (6th November 2014) - Bianchini, Francesca; Calugi, Chiara; Ruzzolini, Jessica; Menchi, Gloria; Calorini, Lido; Guarna, Antonio; Trabocchi, Andrea
Abstract : Ad -proline peptidomimetic targeting MMP-2 and MMP-9 was identified from a pool of compounds following enzyme inhibition kinetics and Matrigel sponge assays, showing the capacity of blocking capillary network formation in vivo . Abstract : Ad -proline peptidomimetic targeting MMP-2 and MMP-9, being involved during tumor cell invasion and angiogenesis, was identified from a pool of compounds following enzyme inhibition kinetics and zymography, clearly highlighting the invasion inhibitory activity and capacity of blocking capillary network formation in vivo .